The Healthy Democracy Kit: design, implementation, uptake, and impact of a novel voter registration toolkit for healthcare settings - Madeline M. Grade; Alexander W. T. Reardon; Yoonhee P. Ha; Adi Steinhart; Alister F. Martin (BMC, 2023)
Abstract Background Access to voting is increasingly recognized as a social determinant of health. Health equity could be improved if healthcare workers (HCWs) routinely assessed the voter registration status of patients during clinical encounters and helped direct them towards appropriate resources. However, little consensus exists on how to achieve these tasks efficiently and effectively in healthcare settings. Intuitive and scalable tools that minimize workflow disruptions are needed. The Healthy Democracy Kit (HDK) is a novel voter registration toolkit for healthcare settings, featuring a wearable badge and posters that display quick response (QR) and text codes directing patients to an online hub for voter registration and mail-in ballot requests. The objective of this study was to assess national uptake and impact of the HDK prior to the 2020 United States (US) elections. Methods Between 19 May and 3 November 2020, HCWs and institutions could order and use HDKs to help direct patients to resources, free of cost. A descriptive analysis was conducted to summarize the characteristics of participating HCWs and institutions as well as the resultant total persons helped prepare to vote. Results During the study period, 13,192 HCWs (including 7,554 physicians, 2,209 medical students, and 983 nurses) from 2,407 affiliated institutions across the US ordered 24,031 individual HDKs. Representatives from 604 institutions (including 269 academic medical centers, 111 medical schools, and 141 Federally Qualified Health Centers) ordered 960 institutional HDKs. Collectively, HCWs and institutions from all 50 US states and the District of Columbia used HDKs to help initiate 27,317 voter registrations and 17,216 mail-in ballot requests. Conclusions A novel voter registration toolkit had widespread organic uptake and enabled HCWs and institutions to successfully conduct point-of-care civic health advocacy during clinical encounters. This methodology holds promise for future implementation of other types of public health initiatives. Further study is needed to assess downstream voting behaviors from healthcare-based voter registration.